A critical analysis of Bloom’s taxonomy in teaching creative and critical thinking skills in Malaysia through English literature - Abdul Rahman, Shukran; Abdul Manaf, Nor Faridah (Canadian Center of Science and Education, 2017)
Purpose: The study aims to (1) review the literature that analyses the relevance of Bloom’s Taxonomy of Educational Objectives in the teaching of creative and critical thinking among students in Malaysia, and (2) identify missing aspects in Bloom’s Taxonomy vis a vis the indigenous context, important to promote creative and critical thinking among students in Malaysia.